Longevity effect of a polysaccharide from Chlorophytum borivilianum on Caenorhabditis elegans and Saccharomyces cerevisiae - Pannakal, S; Jäger, S; Duranton, A; Tewari, A; Saha, S; Radhakrishnan, A; Roy, N; Kuntz, J; Fermas, S; James, D; Mellor, J; Misra, N; et al. (Public Library of Science (PLoS), 2017)
The traditional Indian medicine, Ayurveda, provides insights and practical solutions towards a healthy life style. Rasayana is a branch of Ayurveda known for preserving and promoting health, enhancing the quality of life and delaying the aging process. In the traditional knowledge, the Rasayana herb, Chlorophytum borivilianum (C. borivilanum) is regarded as a general health promoting tonic that delays aging and increases lifespan, cognitive function and physical strength. Aging is a complex and multifactorial physiological phenomenon that manifests itself over a wide range of biological systems, tissues, and functions. Longevity is an obvious marker of physiological aging. Simple model systems such as the single-cell budding yeast Saccharomyces cerevisiae (S. cerevisiae) and the nematode, Caenorhabditis elegans (C. elegans) are widely used to study the aging process and longevity. Here, we show that a polysaccharide fraction obtained from C. borivilianum increases the lifespan of S. cerevisiae and C. elegans, using an automated screening platform (ChronoscreenTM). Chemical analysis of this extract revealed a low molecular weight polysaccharide of 1000 Da, predominantly comprising Glu1→6Glu linkage. This polysaccharide showed significant dose-dependent extension of the median lifespan of S. cerevisiae by up to 41% and of the median lifespan of C. elegans by up to 10%. Taking cue from these results and the traditionally described benefits of Rasayanas on skin rejuvenation, we tested in vitro the polysaccharide for potential skin benefits. In a keratinocyte culture, we observed that this polysaccharide increased cell proliferation significantly, and induced synthesis of hyaluronic acid (HA), a well-known extracellular matrix component. Furthermore, when added to culture medium of human reconstructed epidermis, we observed an enhanced production of epidermal markers, e.g. CD44 and HA that are otherwise diminished in aged skin. Together, these results suggest that in addition to life-span extension of S. cerevisiae and C. elegans, a polysaccharide from the Rasayana herb, C. borivilianum may have beneficial effects on skin aging parameters.